Dean Acheson : a life in the Cold War - Beisner, Robert L. (OUP E-Books., 2006)
Dean Acheson was one of the most influential Secretaries of State in U.S. history, presiding over American foreign policy during the pivotal decade after World War II. During his vastly influential career, Acheson spearheaded the greatest foreign policy achievements in modern times, ranging from the Marshall Plan to the establishment of NATO. In a book filled with insight based on research in government archives, memoirs, letters, and diaries, historian Beisner illuminates Acheson's policy-making, describing how he led the State Department and managed his relationship with Truman. The book examines Acheson's major triumphs, including the highly underrated achievement of converting West Germany and Japan from mortal enemies to prized allies, and does not shy away from examining his missteps. But underlying all his actions, Beisner shows, was a tough-minded determination to outmatch the strength of the Soviet bloc--indeed, to defeat the Soviet Union at every turn.--From publisher description.